Clinical outcomes of children with Wilms tumor treated on a SIOP WT 2001 protocol in a tertiary care hospital in south India. Issue 6 (December 2018) - John, Rikki; Kurian, Jujju Jacob; Sen, Sudipta; Gupta, Manish Kumar; Jehangir, Susan; Mathew, Leni Grace; Mathai, John
Summary: Introduction: Wilms tumor is the most common pediatric renal malignancy. While developed countries have had excellent survival, it remains poorer by comparison in developing countries. The aim was to analyze the clinical outcome of children with Wilms tumor managed in a developing country from 2004 to 2014 by the SIOP WT 2001 protocol. Methods: Fifty-nine children with Wilms tumor managed by a SIOP WT 2001 regimen from 2004 to 2014 were analyzed. Results: The median age at presentation was 36 months, and 59% were boys. The average size of the tumor at presentation was 523 mL. Inferior vena cava thrombus was present in 11, distant metastases in 18, and bilateral tumors in six. Preoperative chemotherapy was given to all children after a diagnostic core needle biopsy. Preoperative chemotherapy reduced the tumor size to a mean of 208 mL and resolved venacaval thrombus in eight. Fifty-five children underwent definitive surgery while two children died during preoperative chemotherapy and two remained inoperable. All surviving children received adjuvant chemotherapy with 17 receiving radiotherapy as well. The overall survival (OS) was 80% and the event-free survival (EFS) was 73% after a mean follow up of 42 months after completion of therapy. Discussion: The tumor volumes at presentation and the incidence of venous tumor thrombosis in our cohort were much higher than those reported from developed countries. The incidence of metastatic disease at diagnosis (30.5%) was significantly higher than the 10–12% reported in Western data, but similar to that reported from various developing countries (14.1–31%). The OS in our cohort was 80% and the EFS was 73% with there being no events after 28 months. Although the survival rate for localized disease is similar to that in developed countries, the OS for metastatic disease was significantly less (50% vs. 75%). We also found that using an upfront posterior flank core biopsy was safe and beneficial for differentiating Wilms tumor from other pediatric renal tumors that are less chemosensitive. Conclusion: In a resource-restricted environment such as ours, the SIOP WT 2001 protocol has been found to show excellent results.Figure Summary of the cases treated from 2004 to 2014.